Application of Autonomous Sensory Meridian Response Relaxation to Reduce Pain Intensity in Post-Hemorrhoid Surgery Patients - Yuli Yanti; Diah Ayu Kuswaryani; Hanny Irmaya (GLOBAL HEALTH SCIENCE GROUP, 2023)
Hemorrhoids are a condition in which the veins in the rectum and anus become swollen and inflamed, causing discomfort and bleeding. If left untreated, hemorrhoids will protrude permanently (grade IV hemorrhoids) and the only therapy for this condition is hemorrhoidectomy. However, excision after hemorrhoidectomy surgery often causes extreme pain. Based on data from the Ministry of Health in 2018, it is estimated that in 2030 there will be 21.3 million people in Indonesia suffering from hemorrhoids. The purpose of this study was to determine the application of autonomous sensory meridian response (ASMR) to reduce pain intensity after hemorrhoid surgery. This type of research is descriptive with a case study approach model. The sample was 3 respondents after hemorrhoidectomy surgery who experienced severe pain. Data is collected by means of observation and measurement. Analysis is carried out in the form of diagnosis and nursing care. In respondents I, II, III before ASMR therapy, the pain scale felt after hemorrhoid surgery was a scale of 8, with severe pain intensity. Then after being given ASMR therapy for 10 minutes, in respondents I-II, the pain intensity felt was severe in the range (7-8) decreased to moderate pain in the range (4-6). However, in respondent III, the pain intensity was felt to be stable, namely the severe pain scale, there was no decrease in pain intensity. The results of this study can be concluded that ASMR relaxation has significant benefits in reducing post-hemorrhoid surgery pain if it is carried out on people with an open attitude towards ASMR therapy, enjoying the videos provided, full concentration and carried out in accordance with the SOP (Standard Operating Procedure).